An agile receiver-switching solution for use with parabolic antennas. - Orfei, Alessandro
We present a solution adopted for the Medicina antenna to carry out the fast, remote, and automatic change of many microwave receivers used for observation in radio astronomy. This new setup allows the capability to switch receivers located at the antenna's primary and secondary foci in a couple of minutes, without the need of manpower or equipment, and regardless of weather constraints.
Keywords: Reflector antenna feeds; Reflector antenna mechanical factors; Reflector antennas; Multireflector antennas; Microwave receivers; Radio astronomy